2006
DOI: 10.1172/jci27352
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal ABCA1 directly contributes to HDL biogenesis in vivo

Abstract: Plasma HDL cholesterol levels are inversely related to risk for atherosclerosis. The ATP-binding cassette, subfamily A, member 1 (ABCA1) mediates the rate-controlling step in HDL particle formation, the assembly of free cholesterol and phospholipids with apoA-I. ABCA1 is expressed in many tissues; however, the physiological functions of ABCA1 in specific tissues and organs are still elusive. The liver is known to be the major source of plasma HDL, but it is likely that there are other important sites of HDL bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
353
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(372 citation statements)
references
References 63 publications
16
353
0
3
Order By: Relevance
“…1) (91, 93). The importance of ABCA1 in the biogenesis of HDL in the intestine was demonstrated by deleting intestinal Abca1, which resulted in a 30% decrease in plasma HDL cholesterol levels (24). Enterocytes deficient in ABCA1 absorb smaller amounts of cholesterol (24).…”
Section: Cholesterolmentioning
confidence: 99%
See 1 more Smart Citation
“…1) (91, 93). The importance of ABCA1 in the biogenesis of HDL in the intestine was demonstrated by deleting intestinal Abca1, which resulted in a 30% decrease in plasma HDL cholesterol levels (24). Enterocytes deficient in ABCA1 absorb smaller amounts of cholesterol (24).…”
Section: Cholesterolmentioning
confidence: 99%
“…The measurement of cholesterol in lymph led to the hypothesis that HDL is not important in cholesterol transport. However, Brunham et al (24) recently demonstrated that the HDL in lymph is dependent on the activity of hepatic ABCA1 and enters the lymph from plasma. Thus, quantification of HDL in lymph may not provide an accurate assessment of the extent of cholesterol absorption via this pathway.…”
Section: Cholesterolmentioning
confidence: 99%
“…Widely reported models for lipid metabolism investigations are hepatocytes and adipocytes, even though the digestion and absorption of dietary lipids, as well as their re-synthesis and packaging for transport, take place in the intestine. The same tissue, together with the liver, controls the cholesterol homeostasis and plasma cholesterol levels, and contributes to the HDL-CL levels [7,8]. The interest for a better characterization of the metabolic switches that regulate the onset and the evolution of lipid dismetabolisms in metal deficiencies prompted us to analyze the intestinal transcriptome in order to identify reliable genetic markers for the early diagnosis and, hopefully, for more effective early treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Absence of functional ABCA1 reduced plasma HDL-C concentrations by ∼95% in humans and mice (Oram 2000;Brunham et al 2006), suggesting ABCA1 is quantitatively the most important factor in maintaining plasma HDL-C levels. In particular, as ABCA1 in the liver accounts for ∼80% of plasma HDL-C levels , hepatic expression of ABCA1 was evaluated to gain an insight into a potential contribution of hepatic ABCA1 to the HDL metabolism in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, ABCA1 plays a pivotal role in nascent HDL formation. Importantly, deletion of Abca1 in the liver and intestine reduced plasma HDL-C concentrations by ∼80% and ∼30% in mice, respectively, indicating that ABCA1 in these tissues is quantitatively most important for maintaining plasma HDL-C levels Brunham et al 2006). In addition to its role in nascent HDL formation, hepatic ABCA1 has been implicated in HDL catabolism.…”
Section: Introductionmentioning
confidence: 99%